Sex and gender identity differences in psychological job outcomes among salespeople - Tanrikulu, Ceyda (Review of Business Management, 2017)
Purpose – The purpose of this study was to determine whether there was any difference among sex and gender identity groups for salespeople in terms of psychological job outcomes, namely job stress, organizational commitment, intention to leave, and job satisfaction. Design/methodology/approach – Data was collected from salespeople using a survey. The questionnaire used was administered to a convenience sample of pharmaceutical salespeople from south-central region of Turkey, through a self-administered questionnaire. Findings – The findings suggested that there were differences between sex groups in psychological job outcomes except job stress, while there were differences between gender identity groups in all of them. There already exist sex differences and also gender identity differences regarding the job outcomes in sales force. Androgynous individuals have the most appropriate gender identity for sales profession, considering that they had a high level of job satisfaction and organizational commitment and a low level of job stress and intention to leave. Originality/value – The major contribution of this study to the literature and administrative implications is the enrichment of information concerning gender-based similarities and/or differences among salespeople in terms of job outcomes with a new and different approach.